Pengaruh Model Pembelajaran Discovery Learning Berbantuan Media Diorama Terhadap Hasil Belajar IPA Siswa Kelas V SD Negeri 20 Pulubala - Gita Sagita Nani; Abdul Haris Panai; Gamar Abdullah; Kudus; Isnanto (EduInovasi: Journal of Basic Educational Studies, 2024)
The Effect of the Discovery Learning Model Assisted by Diorama Media on Science Learning Outcomes of Fifth Grade Students at SD Negeri 20 Pulubala. Thesis. Department of Elementary Teacher Education. Faculty of Education. Universitas Negeri Gorontalo. The supervisor is Prof. Dr. Abdul Haris Panai, M.Pd., MCE and the co-supervisor is Dr. Gamar Abdullah, S.Si., M.Pd.The research question in this study is "Does the discovery learning model assisted by diorama media affect the science learning outcomes of fifth-grade students at SD Negeri 20 Pulubala?" The type of research used is quantitative research. This study employed the Pre Experimental Design method with the One Group Pretest-Posttest Design. The independent variable in this study is the Discovery Learning model assisted by diorama media, and the dependent variable is science learning outcomes. The population of this study consists of all fifth-grade students at SD Negeri 20 Pulubala, totaling 14 students. Data collection in this study was carried out using a multiple-choice test method. Data analysis in this study included a normality test, hypothesis testing using the t-test, and N-Gain Score test.The normality test showed normal distribution values based on the research results and discussions. Subsequently, hypothesis testing using SPSS 29 yielded a significant value (one-tailed) of 0.001 <0.05, with the criteria that if the significant value is smaller than 0.05, then HO is rejected and H1 is confirmed, meaning that there is an effect of the discovery learning model assisted by diorama media on the science learning outcomes of fifth-grade students at SD Negeri 20 Pulubala. The improvement in student learning outcomes is indicated by an N-Gain Score of 0.63 or 63%, which falls into the moderately effective category.